STUDENTS' PERCEPTIONS OF THE EFFECT OF ICE BREAKING ON ENGLISH LEARNING MOTIVATION - munir (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
This study aims to determine students' perceptions of the impact of ice breaking on motivation to learn English for students at UPT SPF SMPN 27 Makassar. Based on the importance of teaching English in Indonesia as a foreign language. Thus, by doing ice breaking before learning, it is hoped that students can focus on the process of learning English. In this study, the authors used case studies and qualitative research methods. The subjects of this study were five students of class VIII 1, consisting of four girls and one boy. The research instrument is observation and interviews. This research results in students becoming enthusiastic and focused on learning English in class.